Intralesional treatment with mesenchymal stem cells in horses with suspensory ligament desmitis and super cial digital exor tendonitis: a retrospective study - Menezes, Rui Miguel Van Raay Ferraz de Menezes (2021)
Mesenchymal stem cells (MSCs) promote the regeneration of scarless tendon tissue after injury. Various sources have been described and used to obtain MSCs, adipose tissue and bone-marrow are one of the most used. A population of 49 horses, that suffered superficial digital flexor tendonitis or suspensory ligament desmitis and were treated either with the combination of stromal vascular fraction and platelet rich plasma, or with allogenic bone marrow derived MSCs, was analyzed retrospectively. The influence of different factors (age, breed, discipline, injury chronicity, treated structure and type of MSCs used) on the outcome of the therapy was evaluated. The re-injury rate observed on the total population was 4% six months after MSC therapy, and 17,8% after 12 months. The results obtained are similar to results obtained in other studies that evaluated the therapeutic effect of MSCs in horses, encouraging the use of these cells in the treatment of tendinoligamentous disorders; Resumo: Tratamento intralesional com células estaminais mesenquimatosas em cavalos com desmite do ligamento suspensor e tendinite do tendão flexor superficial digital: um estudo retrospetivo. As células estaminais mesenquimatosas (MSCs) promovem regeneração de tecido tendinoso saudável após a lesão. Vários tecidos têm sido usados para obter MSCs, mas o tecido adiposo e a medula óssea têm sido os mais populares. Este estudo analisou retrospetivamente uma população de 49 cavalos, com tendinite do tendão flexor digital superficial ou desmite do ligamento suspensor, que foram tratados com uma combinação de fração estromal vascular com plasma rico em plaquetas, ou com células estaminais mesenquimatosas alogénicas derivadas de medula óssea, avaliando a influência de diversos fatores (idade, disciplina, raça, cronicidade da lesão, estrutura tratada e tipo de células estaminais usadas) sobre o resultado da terapia. A taxa de lesões recidivas na população em estudo era de 4% 6 meses depois do tratamento com células estaminais, e 17,8% após 12 meses. Os resultados obtidos neste estudo são semelhantes a outros estudos que avaliaram o mesmo tipo de terapias.